AN ANALYSIS OF TRANSITIVITY SYSTEM IN STUDENTS' ACADEMIC WRITING TEXTS : A Case Study of International Program on Science Education Students in a State University in Bandung - Salsabila, Felin (2016)
This study entitled 'An Analysis of Transitivity System in Students' Academic Writing Texts' investigated how the students present scientific information in their academic writing seen from the Transitivity System, and what the difficulties are encountered by the students while writing their texts. It was conducted in the English for Academic Purposes class in an International Program of Science Education in a state university in Bandung, West Java, Indonesia. This study is a qualitative study using a case study as the research design. The data were collected from the documents of six students' writing texts from three different categories based on students' achievement during their study. The categories are high achievers, middle achievers, and low achievers. The texts were analyzed using Transitivity System proposed by Halliday (1994) and Eggins (2004). Other theories such as the theory of scientific texts suggested by Halliday & Martin (1993), Martin & Veel (1998), Fang (2005), and Fang (2006), and the theory of text types in science proposed by Martin & Rose (2007), Anderson & Anderson (1997), and Knapp & Watkins (2005) were used in the process of analysing the texts. The findings of this study show that the types of students' writing texts are Descriptive Report and Factorial Explanation Text. Most of the students appeared to have insufficient knowledge about the schematic structure of those texts and they needed some improvements particularly in terms of word choices, text organization, grammatical structure, and writing style. Moreover, the informational density and the abstraction, as the specific features of scientific text realised by the number of content words and nominalization, were not successfully achieved. Based on the findings, it is recommended to teachers in some schools where all subjects are taught in English, especially in content area such as science, to apply explicit teaching about the schematic structures and linguistic features of scientific texts. Moreover, it is also suggested that further research can analyze the features in scientific texts beyond Transitivity system. Keywords: Systemic Functional Linguistic, Transitivity System, Scientific Text.